Documentation of preventive care for pressure ulcers initiated during annual evaluations in SCI. (3rd May 2016) - Guihan, Marylou; Murphy, Deidre; Rogers, Thea J.; Parachuri, Ramadevi; SAE Richardson, Michael; Lee, Kenneth K.; Bates-Jensen, Barbara M.
Abstract : Objective : Community-acquired pressure ulcers (PrUs) are a frequent cause of hospitalization of Veterans with spinal cord injury (SCI). The Veterans Health Administration (VHA) recommends that SCI annual evaluations include assessment of PrU risk factors, a thorough skin inspection and sharing of recommendations for PrU prevention strategies. We characterized consistency of preventive skin care during annual evaluations for Veterans with SCI as a first step in identifying strategies to more actively promote PrU prevention care in other healthcare encounters. Design/setting/participants : Retrospective cross-sectional observational design, including review of electronic medical records for 206 Veterans with SCI admitted to 2 VA SCI centers from January-December, 2011. Outcome measures : Proportion of applicable skin health elements documented (number of applicable elements/skin health elements documented). Results : Our sample was primarily white (78%) male (96.1%), and mean age = 61 years. 40% of participants' were hospitalized for PrU treatment, with a mean of 294 days (median = 345 days) from annual evaluation to the index admission. On average, Veterans received an average of 75.5% (IQR 68-86%) of applicable skin health elements. Documentation of applicable skin health elements was significantly higher during inpatient vs. outpatient annual evaluations (mean elements received = 80.3% and 64.3%, respectively, P > 0.001). No significant differences were observed in documentation of skin health elements by Veterans at high vs. low PrU risk. Conclusion : Additional PrU preventive care in the VHA outpatient setting may increase identification and detection of PrU risk factors and early PrU damage for Veterans with SCI in the community, allowing for earlier intervention.